2012
DOI: 10.1177/1474515112446544
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and beliefs about acute coronary syndrome in patients diagnosed with ACS: an Irish cross-sectional study

Abstract: Despite having experienced an ACS event, overall knowledge levels were poor. Higher knowledge levels were associated with better attitudes and beliefs, indicating the inextricable relationship between all three components. Educational programmes should incorporate all three components so that prompt behaviour can be initiated when symptoms arise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
33
4
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 38 publications
23
33
4
7
Order By: Relevance
“…(23, 24) The findings are also similar to reports of lower knowledge of stroke symptoms among racial/ethnic minorities. (9, 11) In contrast to merely 53% who knew to call 911 if experiencing symptoms of a heart attack in the previous work (2), in this study 89% answered correctly, and there was no difference by FRS or MS.…”
Section: Discussionsupporting
confidence: 83%
“…(23, 24) The findings are also similar to reports of lower knowledge of stroke symptoms among racial/ethnic minorities. (9, 11) In contrast to merely 53% who knew to call 911 if experiencing symptoms of a heart attack in the previous work (2), in this study 89% answered correctly, and there was no difference by FRS or MS.…”
Section: Discussionsupporting
confidence: 83%
“…Other studies found that ACS knowledge was independently correlated with confidence in accessing care when experiencing ACS symptoms, response to the symptoms, and self-perceived risk for ACS (Dracup et al, 2008;O'Brien, O'Donnell, McKee, Mooney, & Moser, 2013). Individuals who are knowledgeable about ACS are more likely to accurately perceive their risk status, and an awareness of personal risk may shorten delay time in seeking care for ACS symptoms (Dracup et al, 2008).…”
mentioning
confidence: 96%
“…[9][10][11]31 Factors influencing delay have been grouped into three domains; i) socio-demographic and clinical factors; ii) cognitive and emotional factors; and iii) social factors. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] These factors include recognition of signs and symptoms, gender, ethnicity, education levels, income, and emotional and social factors. Ethnicity, often categorized or described by country of birth, 32,33 is one of the significant nonmodifiable risk factors for cardiovascular disease.…”
Section: Introduction Backgroundmentioning
confidence: 99%